2001
DOI: 10.1046/j.1365-3083.2001.00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally Regulated Expression of the Transmembrane Adaptor Protein TRIM in Fetal and Adult T Cells

Abstract: TRIM is a recently identified transmembrane adaptor protein which is exclusively expressed in T cells and natural killer (NK) cells. In peripheral blood T cells TRIM has been reported to coprecipitate, comodulate, and cocap with the T‐cell receptor (TCR), suggesting that it is an integral component of the TCR/CD3/ζ complex. Here we investigate the expression of TRIM mRNAs and proteins in developing thymocytes. Two splicing isoforms with open reading frames are observed, namely a full length (TRIM) and a trunca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The larger αβTCR complex, that most likely includes TRIM, was present in primary cells. This is in line with our earlier data showing that TRIM co-caps with CD3 in primary human cells [18] and that TRIM is expressed in murine thymocytes [30]. …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The larger αβTCR complex, that most likely includes TRIM, was present in primary cells. This is in line with our earlier data showing that TRIM co-caps with CD3 in primary human cells [18] and that TRIM is expressed in murine thymocytes [30]. …”
Section: Resultssupporting
confidence: 93%
“…The small human γδTCR complex has a stoichiometry of TCRγδ CD3ε 2 γδζ 2 [2,28]; the larger complex likely has a TCRγδ CD3ε 2 γδζ 2 TRIM 2 stoichiometry. At the double negative stage of T cell development, TRIM is already expressed together with the pre-TCR [30], which also includes ζ. Therefore, it is likely that TRIM also associates with the pre-TCR complex.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that TRIM is exclusively expressed in lymphoid organs (thymus, lymph node, and spleen) (4,19). As shown in Fig.…”
Section: Survival Of Trimmentioning
confidence: 72%
“…Northern blot analysis revealed a strong expression of TRIM mRNA in thymus and to a lesser extent in spleen, lymph nodes, and peripheral blood lymphocytes (78). Also, other minor T‐cell subsets, such as γδ T lymphocytes and NK1.1 + αβ thymic T cells, express TRIM (81). A recent analysis of TRIM expression during thymic development further revealed that both TRIM mRNA and protein are expressed in the very early developmental stages (DN1‐DN2 and DN2, respectively) even before pre‐TCR assembly and signaling capacity are carried out (81).…”
Section: Trimmentioning
confidence: 99%
“…Also, other minor T‐cell subsets, such as γδ T lymphocytes and NK1.1 + αβ thymic T cells, express TRIM (81). A recent analysis of TRIM expression during thymic development further revealed that both TRIM mRNA and protein are expressed in the very early developmental stages (DN1‐DN2 and DN2, respectively) even before pre‐TCR assembly and signaling capacity are carried out (81). In contrast, TRIM mRNA is not detectable in fetal liver or bone marrow and the protein is absent from B lymphocytes, B cell lines, the erythroleukemic cell line K562 or the monocytic cell line U937 (78).…”
Section: Trimmentioning
confidence: 99%